The Effect of Observing Multiple Private Information Outcomes on the Inclination to Cheat - Sandro Casal; Antonio Filippin (Institute of Labor Economics (IZA), 2020)
This paper investigates experimentally how the inclination to cheat changes when agents report the result of multiple realizations of a (private information) stochastic event rather than a single outcome. Extreme outcomes clearly signal opportunistic behavior with multiple realizations. The consequent reputation concerns dramatically reduce cheating by large amounts. Multiple draws, however, erode the intrinsic cost of lying, inducing a widespread inclination to slightly misreport the outcomes in a plausible manner. These two opposite effects are similar in magnitude, on average, but show an interesting gender differentiation implying that multiple realizations can be effective with males but may backfire with females.
Keywords: C81; C91; D82; 330; cheating; reputation concerns; moral self-licensing